BANDITRY IN NIGERIA AND THE TRAUMA OF WOMEN AND CHILDREN IN IDP CAMPS: MEDIA INTERVENTION STATEGIES - IGWE, Jacinta Chinenye; NSUDE, Ifeyinwa; ELEM, Stephen Nwanchor (EBSU Journal of Social Sciences and Humanities, 2024)
The number of women and children in Internally Displaced Persons (IDP) camps in Nigeria has remained a social and economic problem to the wellbeing of the victims and national development. The purpose of this study was to explore the media intervention strategies used by journalists to ameliorate the experiences of the victims. The study employed online survey research method. It was anchored on Social Cognitive and Routine Activities Theories. Three research questions were addressed. The study found that the women and children displaced by the bandits in Northern Nigeria suffer various forms of trauma; the journalists in the Northern part of Nigeria employ different media intervention strategies; the media intervention strategies used in assuaging trauma in IDP camp were successful. It recommended that the government of Nigeria should provide adequately for people in IDP camps; the media should sustain its campaigns against banditry; there is need for the media to explore more strategies to reduce trauma in IDP camps.